An experimental study focusing on mindfulness to capture how our contacts with dogs can promote human well-being - Catherine E. Amiot; Mylène Quervel-Chaumette; Christophe Gagné; Brock Bastian (Scientific Reports)
Abstract Pet ownership per se has not been reliably associated with increased human well-being and health. Furthermore, the specific psychological mechanisms and behavioral dynamics through which the presence of pets could yield higher human wellness remain under-investigated. Conducted among dog owners and their dogs, the current experiment investigates if a specific psychological factor – i.e., mindfulness – activated in the presence of one’s dog increases dog owners’ psychological well-being. The study also explores which affiliative and synchronization behaviors manifested within the human–dog dyad are associated with higher human well-being. A within-participants design was employed among 52 dog owners and their dogs. The mindfulness condition was found to have a positive impact on dog owners’ well-being. This condition also generated more affiliative and synchronization behaviors among both owners and their dogs on a majority of behaviors, with some of these behaviors (i.e., frequency the dog initiated contact with their owner; duration the owner communicated with their dog) mediating the associations between the mindfulness induction and the well-being outcomes. These findings confirm the importance of investigating the psychological and behavioral factors which, when activated and manifested within human–dog relationships, promote human wellness as well as interspecies interactivity.